STUDI KASUS : ASUHAN KEBIDANAN KOMPREHENSIF PADA NY.I UMUR 20 TAHUN DI PUSKESMAS WATUMALANG WONOSOBO - Noviana Rizki; Farihah Indriani; Indrawati Aris Tyarini; Dewi Candra Resmi; Ari Setyawati (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2022)
The Maternal Mortality Rate (MMR) is an indicator used to determine the health status of pregnant, maternity and postpartum women, the World Health Organization (WHO) and the National Family Planning Coordinating Board (BKKBN) state that the distance between pregnancies should be two to three years. two years, it can have a negative impact on the health of the mother and fetus, knowing that a close pregnancy distance can pose a risk to pregnant women and the fetus, therefore comprehensive midwifery care is carried out on Ny. I. The purpose of this study is to provide comprehensive midwifery care using the SOAP midwifery care management approach at the Watumalang Health Center, Wonosobo Regency starting from pregnancy to family planning. This report is designed in a descriptive form with a continuity of care approach. The research subject in this case is Mrs. I was 20 years old G2P1A0 with a pregnancy distance of less than two years at the Watumalang Health Center. From the results of the comprehensive midwifery care assessment, during pregnancy, Mrs I had a risk for her pregnancy because the pregnancy distance was too close, less than 2 years. Conclusions on comprehensive midwifery care were found there is a risk that can occur to the mother and fetus because the pregnancy distance is too close.